THE EFFECTIVENESS OF LEARNING MATHEMATICS AT ISLAMIC BOARDING SCHOOLS IN SIAK HULU DISTRICT DURING THE COVID-19 PANDEMIC - mawaddaturrohmah (UIR PRESS, 2021)
This study aims to describe quantitatively the learning of mathematics that was carried out online and offline at Islamic Boarding Schools in the Kampar Regency. This research is quantitative research with an ex-post fact approach. The population of this research was all students in Islamic boarding schools in Kampar Regency. The sample was students at al-Ikhsan boarding schools in the Siak Hulu sub-district, Kampar district. The data collection technique used is the documentation of student learning outcomes from offline and online mathematics learning. Data analysis used quantitative descriptive and T-test. The results of the analysis show that of the 27 students who take online or online learning, 78% of students pass minimum passing criteria with a score above 75. Of 27 students who take online learning, 61.71% pass the minimum passing criteria with a score of 75. The results of the t-test analysis show that there are differences in learning that were carried out online and offline where offline learning is more effective at al-Ikhsan Islamic Boarding School, Siak Hulu District.